Prevalence and Incidence of Multiple Sclerosis in Tehran, Iran - Sharareh ESKANDARIEH; Pouria HEYDARPOUR; Seyedeh-Robab ELHAMI; Mohammad Ali SAHRAIAN (Tehran University of Medical Sciences, 2017)
Background: Tehran is the capital of Iran with an increasing Multiple Sclerosis (MS) incidence. A retrospective population-based study was conducted to evaluate the status of MS prevalence and MS incidence trends in Tehran Province, Iran. Methods: A population-based study was conducted from 1991 to 2014 in Tehran Province, the capital city of Iran based on Iranian MS Society (IMSS) registry system. A structured questionnaire design to cover the important epidemiological variables, related at the individual level for MS. A Monte Carlo Permutation method was utilized to test whether the apparent change in MS trends during 1991-2014 was statistically significant. Results: MS incidence was significantly increased during our study period. The annual percent change (APC) was 12.8% in women during 1991 to 2004 and 12.5% in men during the same period. The point prevalence of MS was 101.39 per 100000 populations in 2014. The age-adjusted prevalence rates were 134.03 and for male patients were 42.45 per 100000. Conclusion: MS prevalence and incidence in Tehran are markedly rising, it is crucial to elucidate the causes of the increasing trends and implement efficient policies lowering disease burden.